KEABSAHAN KONTRAK JUAL BELI RUMAH SUSUN DENGAN SISTEM PRE PROJECT SELLING - Lintang Yudhantaka (Yuridika, 2017)
Nowadays, most of the developers use Pre Project Selling system in selling a flat. Pre Project Selling system is the selling before the property was constructed in which the property is still in the form of images or concepts. This system is always related with a Binding Sale and Purchase Agreement (PPJB). To make a PPJB, a requirements that regulated in Law Number 20 of 2011 about Flat should be fulfilled. If those requirements are not fulfilled, it will certainly has the potential to harming the parties, especially the purchaser. Usually, PPJB is a standard contract that was made unilaterally by the developer and tends to ignoring the interest of the purchaser. The objective of this research is to know about the validity of PPJB. This Article user descriptive analysis method. The conclusion is that PPJB is valid when the requirements in Law Number 20 of 2011 about Flat has been fulfilled.